2015
DOI: 10.3945/ajcn.114.102905
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary patterns during pregnancy and body composition of the child at age 6 y: the Generation R Study

Abstract: Our results suggest that the associations between maternal dietary patterns during pregnancy and body composition of the child at age 6 y are to a large extent explained by sociodemographic and lifestyle factors of mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…Children of mothers who consumed a latent class 3 diet had an increased risk of being overweight or obese at 3 y of age; however, associations were attenuated after adjustment for important prenatal factors. Similarly, data from the Generation R study, a prospective cohort study in Dutch mother-child pairs, did not observe an association between maternal dietary patterns and child body composition at 6 y of age after adjustment for confounding factors, which included both maternal and childhood factors (12). Our study did not adjust for childhood factors because of our interest in the total effect of maternal dietary patterns on child growth variables, and childhood factors are potentially mediators of this association.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Children of mothers who consumed a latent class 3 diet had an increased risk of being overweight or obese at 3 y of age; however, associations were attenuated after adjustment for important prenatal factors. Similarly, data from the Generation R study, a prospective cohort study in Dutch mother-child pairs, did not observe an association between maternal dietary patterns and child body composition at 6 y of age after adjustment for confounding factors, which included both maternal and childhood factors (12). Our study did not adjust for childhood factors because of our interest in the total effect of maternal dietary patterns on child growth variables, and childhood factors are potentially mediators of this association.…”
Section: Discussionmentioning
confidence: 60%
“…Maternal dietary patterns during pregnancy were related to birth weight in 2 early studies in Danish and Japanese pregnant women (9,10); however, this association was not supported in a follow-up study in a diverse pregnancy cohort in the southern region of the United States (11). Similarly, a recent study that used data from the Generation R study found no association between maternal dietary patterns and child body composition at 6 y of age (12).…”
Section: Introductionmentioning
confidence: 95%
“…[118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] Overall, although poor quality diets seem to have detrimental effects in the offspring, they are unlikely to be mediators of changes associated with maternal obesity but probably represent an independent risk factor. Studies have also evaluated the association between type of dietary fat and child health outcomes.…”
Section: Dietary Patterns and Nutrient Changesmentioning
confidence: 99%
“…Retrospective studies have indicated that babies exposed to overnutrition during gestation have higher risks of developing obesity, diabetes and other complications in adult life. 1316 In animal models, offspring of mothers exposed to overnutrition have common phenotypes that include catch-up growth, increased adiposity, impaired glucose tolerance, impaired insulin sensitivity and liver dysfunction. 5,1720 Therefore, it is suggested that prevention of obesity may need to begin before pregnancy, 2125 and thus there is an emerging need to evaluate the impact of maternal diet structure on offspring obesity and the risk of associated disorders.…”
Section: Introductionmentioning
confidence: 99%